Drawn from the Antique : Artists and the classical ideal ; [an exhibition at Teylers Museum, Haarlem, 11 March - 31 May 2015, Sir John Soane's Museum, London, 25 June - 26 September 2015] (Sir John Soane's Museum, 2015)
"This catalogue examines one of the most important educational tools and sources of inspiration for Western artists for over five hundred years: drawing after the Antique. From the Renaissance to the 19th century, classical statues offered young artists idealised models from which they could learn to represent the volumes, poses and expressions of the human figure and which, simultaneously, provided perfected examples of anatomy and proportion. For established artists, antique statues and reliefs presented an immense repertory of forms that they could use as inspiration for their own creations. Through a selection of thirty-nine drawings, prints and paintings, covering more than four hundred years and by artists as different as Federico Zuccaro, Hendrick Goltzius, Peter Paul Rubens, Charles-Joseph Natoire, Henry Fuseli and Joseph Mallord William Turner, this catalogue provides the first overview of a phenomenon crucial for the understanding and appreciation of European art."--Page 2 of cover